Common Chinese Materia Medica Volume 4 - Ye, Huagu; Li, Chuyuan; Ye, Wencai; Zeng, Feiyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This fourth volume describes 256 species of medicinal plants from 5 families, which are commonly used in Chinese medicine. The most important species are Agrimonia pilosa, Amygdalus persica, Armeniaca mume, Armeniaca vulgaris, Armeniaca sibirica, Chaenomeles sinensis, Eriobotrya japonica of Rosaceae; Chimonanthus praecox of Calycanthaceae$1!+9(BAlbizia julibrissin, Archidendron clypearia, Entada phaseoloides, Bauhinia championii of Mimosoideae; Caesalpinia sappan, Cassia tora, Gleditsia sinensis of Caesalpiniaceae; Abrus cantoniensis, Astragalus membranaceus, Astragalus membranaceus, Dalbergia odorifera, Desmodium caudatum, Desmodium styracifolium, Erythrina variegata, Euchresta japonica, Flemingia prostrata, Glycyrrhiza uralensis, Glycyrrhiza inflata, Glycyrrhiza glabra, Lablab purpureus, Sophora japonica and Spatholobus suberectus of Butterflyaceae. In each specie, it introduces the scientific names, medicinal names, morphologies, habitats, distributions, acquisition and processing methods of these medicinal plants, the content of medicinal properties, therapeutic effects, usage and dosage of these medicinal plants, and attaches unedited color pictures and pictures of part herbal medicines of each species. This book series has 10 volumes in total, which covers over 2000 kinds of Chinese medicines that are commonly used. These volumes not only introduce the efficacy function and some prescriptions of the medicines, but also introduce the biological characteristics of them in detail with clear photos of the habitats, so that readers can identify them in the field. Apart from the growing environment, the books expound the distribution areas and other information to facilitate researches and other applications. The volumes are targeted at readers of general interests and it is also of high referential value for scientific researcher and teachers. It can be used as a guide to researchers, clinical doctors, and students in the department of pharmaceutics and traditional Chinese medicine.s
Agrimonia pilosa -- Amygdalus persica -- Armeniaca mume -- Armeniaca vulgaris -- Armeniaca sibirica -- Chaenomeles sinensis -- Eriobotrya japonica of Rosaceae; Chimonanthus praecox of Calycanthaceae$1!+9(BAlbizia julibrissin -- Archidendron clypearia -- Entada phaseoloides -- Bauhinia championii of Mimosoideae; Caesalpinia sappan -- Cassia tora -- Gleditsia sinensis of Caesalpiniaceae; Abrus cantoniensis -- Astragalus membranaceus -- Astragalus membranaceus -- Dalbergia odorifera -- Desmodium caudatum -- Desmodium styracifolium -- Erythrina variegata -- Euchresta japonica -- Flemingia prostrata -- Glycyrrhiza uralensis -- Glycyrrhiza inflata -- Glycyrrhiza glabra -- Lablab purpureus -- Sophora japonica and Spatholobus suberectus of Butterflyaceae.s
Keywords: Pharmacy; Plants$1 (BEvolution.s; Medicine; Pharmacy; Plant Evolution; Clinical Medicine; Materia Medica